2007
DOI: 10.1007/s11743-007-1045-3
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption of Anionic–Cationic Surfactant Mixtures on Metal oxide Surfaces

Abstract: This research evaluates the adsorption of anionic and cationic surfactant mixtures on charged metal oxide surfaces (i.e., alumina and silica). For an anionic-rich surfactant mixture below the CMC, the adsorption of anionic surfactant was found to substantially increase with the addition of low mole fractions of cationic surfactant. Two anionic surfactants (sodium dodecyl sulfate and sodium dihexyl sulfosuccinate) and two cationic surfactants (dodecyl pyridinium chloride and benzethonium chloride) were studied … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
28
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(31 citation statements)
references
References 43 publications
3
28
0
Order By: Relevance
“…The results showed that the adsorption of anionic surfactant increased after mixing with cationic surfactant on sandstone, while adsorption of cationic surfactant on sandstone can be substantially reduced on negatively charged surfaces when present in anionic-rich surfactant mixtures above the CMC. The adsorption result of S a-c looks like cationic surfactant is ''sequestered'', which is similar to results from Upadhyaya (2007). For alkalinesurfactant-polymer (AS a-c P) system, the adsorption amounts for both anionic surfactant A and cationic surfactant C were further reduced to 0.04mg/g and 0.07mg/g sand, respectively.…”
Section: Adsorption Of Mixtures Of Anionic-cationic Surfactants On Sasupporting
confidence: 76%
See 1 more Smart Citation
“…The results showed that the adsorption of anionic surfactant increased after mixing with cationic surfactant on sandstone, while adsorption of cationic surfactant on sandstone can be substantially reduced on negatively charged surfaces when present in anionic-rich surfactant mixtures above the CMC. The adsorption result of S a-c looks like cationic surfactant is ''sequestered'', which is similar to results from Upadhyaya (2007). For alkalinesurfactant-polymer (AS a-c P) system, the adsorption amounts for both anionic surfactant A and cationic surfactant C were further reduced to 0.04mg/g and 0.07mg/g sand, respectively.…”
Section: Adsorption Of Mixtures Of Anionic-cationic Surfactants On Sasupporting
confidence: 76%
“…To date, only a limited number of adsorption studies have been conducted with mixtures of anionic-cationic surfactants (Fuangswasdi et al, 2006;Upadhyaya et al, 2007;Zhang et al, 2006). Huang et al (1989) have found that the adsorption of both cationic and anionic surfactants on silica can be promoted by coadsorption of cationic surfactants.…”
Section: Adsorption Of Mixtures Of Anionic-cationic Surfactants On Samentioning
confidence: 99%
“…These lower salinities are challenging because it is difficult to find surfactants for producing ultralow crude-oil/water IFT at such reservoir conditions. Recently, it has been possible to obtain suitable surfactants for harsh reservoir conditions of elevated temperature and hardness with large/bulky hydrophobes, such as polymeric surfactants (Wang et al 2010;Zhang and Tang 2010;Elraies et al 2011;Elraies and Tan 2012), dimeric (gemini) and oligomeric surfactants (Bae and Chou 1989;Zana 2002;Iglauer et al 2010;Gao and Sharma 2012;Wei 2012), Guerbet alkoxy sulfates and Guerbet alkoxy carboxylates (Adkins et al 2012;Lu et al 2012), and alkoxy carboxylates and/or sulfonates (Berger and Berger 2007;Berger et al 2009;Weerasooriya and Pope 2012) made from alkoxylating with propylene oxide and ethylene oxide groups. By tuning propylene oxide and ethylene oxide numbers or the use of multiple hydrophilic groups in surfactant molecule, it is possible to obtain the suitable hydrophilic-lipophilic balance needed to achieve ultralow IFT as well as other performance characteristics needed for efficient oil recovery.…”
Section: Introductionmentioning
confidence: 99%
“…Mixtures of anionic and cationic surfactants have been widely used in detergency and fabric softening, analytical chemistry, enhanced oil recovery, and pharmaceutical applications [1][2][3][4][5][6][7]. Mixtures of anionic and cationic surfactants can exhibit greater synergism than other mixed systems (anionic-anionic, cationic-cationic, ionic-nonionic, and nonionic-nonionic): they have the potential for much lower critical micelle concentration (CMC) than either of the anionic and cationic surfactant components [2][3][4][5][6][7]; they are usually more surface active (low interfacial tension, IFT) than individual surfactants; and they can also produce microstructures not formed by pure components D such as vesicles and rod-like micelles [7].…”
Section: Introductionmentioning
confidence: 99%
“…Mixtures of anionic and cationic surfactants can exhibit greater synergism than other mixed systems (anionic-anionic, cationic-cationic, ionic-nonionic, and nonionic-nonionic): they have the potential for much lower critical micelle concentration (CMC) than either of the anionic and cationic surfactant components [2][3][4][5][6][7]; they are usually more surface active (low interfacial tension, IFT) than individual surfactants; and they can also produce microstructures not formed by pure components D such as vesicles and rod-like micelles [7]. However, the limitation of these mixed systems is their tendency to form crystalline precipitates in aqueous solution as a result of the coulombic interaction between oppositely charged species [1,[7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%